2019
DOI: 10.1186/s12961-019-0492-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of instruments for the analysis of national-level physical activity and sedentary behaviour policies

Abstract: BackgroundThis systematic review aimed to identify and critically assess available instruments for the analysis of national-level physical activity (PA) and sedentary behaviour (SB) policies and provide recommendations for their future use.MethodsWe conducted a systematic search of academic and grey literature through six bibliographic databases, Google and the websites of three international organisations for PA promotion to identify instruments that are used or that may be used for national-level PA/SB polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Such areas are strong in bureaucratic sport systems, which was recognized in Poland [ 43 ]. Thus, while the programs are precisely planned in terms of source of financing, responsibility and actions associated with particular goals, the results (outcomes and impact) and effectiveness of the government actions are not evaluated [ 9 ]. In particular, evaluation of some of the programs is only a formality which does not lead to knowledge generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such areas are strong in bureaucratic sport systems, which was recognized in Poland [ 43 ]. Thus, while the programs are precisely planned in terms of source of financing, responsibility and actions associated with particular goals, the results (outcomes and impact) and effectiveness of the government actions are not evaluated [ 9 ]. In particular, evaluation of some of the programs is only a formality which does not lead to knowledge generation.…”
Section: Discussionmentioning
confidence: 99%
“…While the insufficient PA of children and adolescents is commonly considered a global issue, the actual programs to solve the problem primarily occur on a national level [ 9 ]. Efficient policies and programs require up-to-date, valid national-level data to define issues, measure progress, determine intervention tools and evaluate the outcomes of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This would suggest that this dimension of physical activity could potentially be 'measured' and compared both over time and between users when the tool is applied consistently. Pogrmilovic et al (2019), noted both the need for the development of standardised methods for physical activity policy analysis and the relative disproportion of engagement of low-and middle-income countries. Whilst this paper outlines one approach taken in Wales the authors acknowledge the methodological limitations of the system that they have developed for quantifying what is a complex and largely qualitative process.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent review has identified increasing numbers of studies in the field of physical activity policy research that have used a variety of methods for policy analysis (Pogrmilovic, O'sullivan, Milton, Biddle, & Pedisic, 2019), there have been very few validated tools to aid such work (Pogrmilovic et al, 2019). A Policy Analysis Framework was published in 2002 and whilst it paved the way, it was at an early stage of physical activity policy development and was limited in the range of contributing sectors identified in the Framework (Schmid, Pratt, & Witmer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Through compulsory PE lessons and additional organized PE classes, the school enables children to fulfill the recommendations regarding PA [35][36][37]. Moreover, participation in organized PA, especially team games, can bring benefits beyond physical health [32,34,[38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%